Development of the Attitudes to Domestic Violence Questionnaire for Children and Adolescents. (September 2015) - Fox, Claire L.; Gadd, David; Sim, Julius
To provide a more robust assessment of the effectiveness of a domestic abuse prevention education program, a questionnaire was developed to measure children's attitudes to domestic violence. The aim was to develop a short questionnaire that would be easy to use for practitioners but, at the same time, sensitive enough to pick up on subtle changes in young people's attitudes. We therefore chose to ask children about different situations in which they might be willing to condone domestic violence. In Study 1, we tested a set of 20 items, which we reduced by half to a set of 10 items. The factor structure of the scale was explored and its internal consistency was calculated. In Study 2, we tested the factor structure of the 10-item Attitudes to Domestic Violence (ADV) Scale in a separate calibration sample. Finally, in Study 3, we then assessed the test–retest reliability of the 10-item scale. The ADV Questionnaire is a promising tool to evaluate the effectiveness of domestic abuse education prevention programs. However, further development work is necessary.